Decoherence in an interacting quantum field theory: the vacuum case - Koksma, Jurjen F.; Prokopec, Tomislav; Schmidt, Michael G. (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We apply the decoherence formalism to an interacting scalar field theory. In the spirit of the decoherence literature, we consider a “system field” and an “environment field” that interact via a cubic coupling. We solve for the propagator of the system field, where we include the self-energy corrections due to the interaction with the environment field. In this paper, we consider an environment in the vacuum state (T=0). We show that neglecting inaccessible non-Gaussian correlators increases the entropy of the system as perceived by the observer. Moreover, we consider the effect of a changing mass of the system field in the adiabatic regime, and we find that at late times no additional entropy has been generated.